2019
DOI: 10.2147/ott.s208848
|View full text |Cite
|
Sign up to set email alerts
|

<p>OGDH promotes the progression of gastric cancer by regulating mitochondrial bioenergetics and Wnt/β-catenin signal pathway</p>

Abstract: Background/aims2-oxoglutarate dehydrogenase (OGDH) is the first rate-limiting E1 subunit of OGDH complex (OGDHC), which plays as a regulatory point in the cross-road of TCA cycle and glutamine metabolism. Until now, the role of OGDH in carcinogenesis has been unclear.MethodsIn the present study, we determined the expression of OGDH in human gastric cancer (GC) tissues and cell lines by RT-qPCR, Western blotting and immunohistochemical staining respectively. The biological impacts of OGDH on cell growth and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“… 24 OGDH, the host gene of circ-OGDH, plays a regulatory role at the intersection of the TCA cycle and glutamine metabolism. 25 , 26 OGDH played a promoting effect in tumor progression via regulation of mitochondrial bioenergetics and Wnt/beta-catenin pathway in gastric cancer. 26 Our data indicated that circ-OGDH silencing decreased GLS1 protein level, glutamine consumption, α-KG production, and ATP content in ESCC cells, illustrating circ-OGDH facilitated glutamine metabolism in ESCC cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 OGDH, the host gene of circ-OGDH, plays a regulatory role at the intersection of the TCA cycle and glutamine metabolism. 25 , 26 OGDH played a promoting effect in tumor progression via regulation of mitochondrial bioenergetics and Wnt/beta-catenin pathway in gastric cancer. 26 Our data indicated that circ-OGDH silencing decreased GLS1 protein level, glutamine consumption, α-KG production, and ATP content in ESCC cells, illustrating circ-OGDH facilitated glutamine metabolism in ESCC cell.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 OGDH played a promoting effect in tumor progression via regulation of mitochondrial bioenergetics and Wnt/beta-catenin pathway in gastric cancer. 26 Our data indicated that circ-OGDH silencing decreased GLS1 protein level, glutamine consumption, α-KG production, and ATP content in ESCC cells, illustrating circ-OGDH facilitated glutamine metabolism in ESCC cell. Furthermore, circ-OGDH knockdown repressed ESCC cell growth in vivo and constrained ESCC cell proliferation, metastasis, and invasion in vitro, indicating that circ-OGDH played a promoting influence on tumor growth in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of OGDH is shown to associated with gastric cancers and OGDH knockdown interferes with cancer cell proliferation through reducing β-catenin signaling. 41 In the other hands, loss of OGDH was shown to stabilize hypoxia-inducible transcription factor 1α (HIF1α), a key protein for cancer proliferation in hypoxia condition. 42 Burr et al showed that OGDH defects leads to L-2-hydroxygularate (L-2-HG) formation, which inhibits the activity of HIFα prolyl hydroxylases (PHDs), an enzyme that is required for HIF1α degradation in normoxia condition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, knockdown of 2-oxoglutarate dehydrogenase induced mitochondria dysfunction and apoptosis, and inhibited ZEB1 at the same time in GC cells. 36 In another research, ZEB1 was necessary for ROS generation and maintenance of mitochondrial membrane potential. 37 For miR-199a-3p, targets for regulation of apoptosis could be varied.…”
Section: Dovepressmentioning
confidence: 99%